Compare the reaction times of Turkish national team wrestlers - Koç, H.; Aydos, L. (European Journal of Physical Education and Sport Science, 2018)
The purpose of this study is to compares the reaction time abilities in Olympic level male greco-roman and freestyle national team wrestlers. A total of 36 male Turkish wrestlers, 19 greco-roman wrestlers and 17 freestyle wrestlers have participated as volunteers in this study. Statistical analysis of the data was made by SPSS 17.0 statistical package program and Statistical comparison of the Greco-Roman and Freestyle wrestler groups was carried out using Mann Whitney-U test. Spearman's correlation coefficients (r=Spearman's rho) were used to express the relationships between parameters. Acording to results, there were no statistically significant correlation among reaction time and other parameters except agility ability of the wrestlers. Apparently, the reaction time has not affected most of these variables for elite level wrestlers.